PENDAMPINGAN SISWA SEKOLAH DASAR MENGENAL SISTEM PERTAHANAN, DEMOKRASI, DAN NASIONALISME DI BATALYON KAVALERI 2/TC - Gulo, Steven Jacub; Ayub, Stefan Lamuel; Lestari, Sri; Desmon, Timothy; Anthony, Calvin Fritz (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Community Service activity (PKM) aims to provide understanding to elementary school students about Indonesia's defense and security and to increase the sense of nationalism among students of SD Negeri Tegalrejo 04. This PKM was held on Saturday, October 14, 2023, at 08.00-12.00 in collaboration with KODIM 0714 Salatiga. This PKM activity was carried out at the 2/TC Cavalry Battalion, Ambarawa. This activity was attended by 100 elementary school students of Tegalrejo 04 Elementary School. The activity began with materials provided by the Indonesian National Armed Force (TNI) regarding the defense system and also the defense equipment owned by the 2/TC Cavalry Battalion, such as the weapons owned and the types of tanks owned by the 2/TC Cavalry Battalion, such as Ambulance Tanks, Canon Tanks, and Troop Transport Tanks. Furthermore, participants who are elementary school students are also introduced to the uniforms worn by the 2/TC Cavalry Battalion troops. The participants are also introduced to the companies in the Battalion, each of which has a different task. After that, the participants were invited to have a tour the battalion using a tank and were introduced to the training places in the battalion. At the end of the PkM activity, the PKM team, authors of this article, conducted a reflection session with Tegalrejo 04 Elementary School students to hear what they got after participating in a series of activities at the 2/TC Cavalry Battalion.